2020
DOI: 10.3390/genes11070805
|View full text |Cite
|
Sign up to set email alerts
|

Shedding the Light on Litopenaeus vannamei Differential Muscle and Hepatopancreas Immune Responses in White Spot Syndrome Virus (WSSV) Exposure

Abstract: White Spot Syndrome Virus (WSSV) is one of the main threats to farming Litopenaeus vannamei, the most important crustacean commercialized in aquaculture worldwide. Here, we performed RNA-seq analyses in hepatopancreas and muscle from WSSV-negative (healthy) and WSSV-positive (unhealthy) L. vannamei, previously exposed to the virus, to obtain new insights about the molecular basis of resistance to WSSV. We detected 71% of our reads mapped against the recently described L. vannamei genome. This is the first repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 85 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…LvRab11 expression was observed in all the tissues tested in the shrimp but at different levels. Hepatopancreas tissue is important for the production of immune response molecules, it does not only initiate humoral immune, but also play an important role in cellular immune response 36 , 37 . In hepatopancreas, LvRab11 and 14-3-3ε expression profile were significantly increased in the late stage of WSSV stimulation (48 hpi), therefore, we imply that LvRab11 and 14-3-3ε represents a supplemental immune molecule that functions in the late stage of WSSV infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LvRab11 expression was observed in all the tissues tested in the shrimp but at different levels. Hepatopancreas tissue is important for the production of immune response molecules, it does not only initiate humoral immune, but also play an important role in cellular immune response 36 , 37 . In hepatopancreas, LvRab11 and 14-3-3ε expression profile were significantly increased in the late stage of WSSV stimulation (48 hpi), therefore, we imply that LvRab11 and 14-3-3ε represents a supplemental immune molecule that functions in the late stage of WSSV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the expression level of 14-3-3 isoform was upregulated after virus infection, and overexpression of 14-3-3 protein could reduce the production of virus particles 4 , 38 , 39 . Santos et al 36 reported that genes upregulated in hepatopancreas and in healthy shrimp (shrimps exposed to the virus but not infected) are likely to be involved in response to WSSV and are central ones in keeping shrimps WSSV free. Whereas downregulation of LvRab11 in early stage in this tissue may imply that the virus may inhibit this gene to favor its replication in the initial stage 40 .…”
Section: Discussionmentioning
confidence: 99%
“…With the emergence of various omics, transcriptomics has become an important element in understanding biological information. In recent years, many studies have been conducted to reveal the underlying molecular mechanisms that cause WSSV to be detrimental to crustaceans through transcriptomics (Rao et al, 2015), including Litopenaeus vannamei infected with WSSV (Santos et al, 2020) and Macrobrachium Rosenbergii infected with WSSV (Rao et al, 2015). These studies have identified genetic factors and immune signaling pathways that may be implicated in resistance to WSSV and provided additional insights into the prevention and treatment of WSSV.…”
Section: Introductionmentioning
confidence: 99%